The road to molecular identification and detection of fungal grapevine trunk diseases - Azevedo-Nogueira, Filipe; Rego, Cecília; Gonçalves, Helena Maria Rodrigues; Fortes, Ana Margarida; Gramaje, David; Martins-Lopes, Paula (Frontiers in Plant Science, 2022)
Grapevine is regarded as a highly profitable culture, being well spread worldwide and mostly directed to the wine-producing industry. Practices to maintain the vineyard in healthy conditions are tenuous and are exacerbated due to abiotic and biotic stresses, where fungal Grapevine Trunk Diseases (GTDs) play a major role. The abolishment of chemical treatments and the intensification of several management practices led to an uprising in GTDs outbreaks. Symptomatology of GTDs is very similar among diseases, leading to underdevelopment of the vines and death in extreme scenarios. Disease progression is widely affected by biotic and abiotic factors and prevalence of the pathogens are variable regarding country and region. In this review, the state-of-the-art regarding GTDs identification and detection is vastly analysed. Methods and protocols used for GTDs identification, which are currently rather limited, are highlighted. The main conclusion is the utter need for the development of new technologies to easily and precisely detect the presence of the pathogens related to GTDs, allowing to readily take phytosanitary measures and/or to proceed to plant removal in order to establish better vineyard management practices. More, new practices and methods of detection, identification and quantification of infectious material would allow to impose a greater control in nurseries and plant exportation, limiting the movement of infected vines, hence avoiding the propagation of fungal inoculum throughout wine regions.